Judicial creativity at the International Criminal Tribunals - Darcy, Shane; Powderly, Joseph (Oxford : Oxford University Press, 2011)
As the work of the International Criminal Tribunals for the Former Yogoslavia and Rwanda draws to a close, this collection appraises their impact. It particularly focuses on the position of judges as lawmakers within these tribunals, shedding light on the profound changes in international criminal law which these judges have instigated.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Judge-made law; Criminal jurisdiction; International offenses; International Tribunal for the Prosecution of Persons Responsible for Serious Violations of International Humanitarian Law Committed in the Territory of the Former Yugoslavia since 1991.; International Criminal Tribunal for Rwanda